Space Sciences Laboratory, University of California at Berkeley, Berkeley, CA, 94720 - Tennyson, Elizabeth M.; Sallmen, Shauna; Korpela, Eric (Proceedings of the Wisconsin Space Conference, 2011)
One of the many processes that occur in our Milky Way Galaxy is the in- teraction of Neutral Hydrogen (H I) shells with the Interstellar Medium (ISM). H I shells are formed when material from stellar winds and supernova explosions expands outward and mixes with the ISM. Without this phenomenon the heavy elements made in stars would not be recycled and reused for future star and planet systems. The goal of this project is to better understand how interstellar shells evolve. To acquire a better grasp of a shell’s characteristics and develop- ment, we compared images for 55 shells that were discovered in the Search for Extraterrestrial Neutral Hydrogen (SETHi) radio database. The SETHi images show cold, neutral gas, the H-Alpha Composite Survey images show warm, ion- ized gas, the IRIS (infrared) images show warm dust, and the RASS (X-ray) images reveal hot gas. The initial comparison identified nine potentially interest- ing shells. Of these, four are most suitable for detailed follow-up study, based on information available from their kinematic distances. We present a catalog of the shells we classified, including details of those that are likely targets. Follow-up detailed multi-wavelength comparisons can give us estimates on a shells’s age and evolutionary status.